A novel lysosome‐localized fluorescent probe with aggregation‐induced emission without alkalinizing effect. (30th July 2021) - Zhang, Jingran; Jia, Yan; Xing, Xinyi; Qin, Mengmei; Wu, Zibo; Zhong, Yingqian; Liu, Lele; Sun, Shuqing; Li, Peng; Wang, Haiyuan; Zhao, Guangjiu
Abstract: Herein, a novel small molecule probe, tetraphenylethylene‐cystein (TPE‐Cys), was rationally designed and developed for the intracellular lysosome localization. The combination of tetraphenylethylene and cysteine serve as a novel strategy for lysosome‐targeting, with significant aggregation‐induced emission increases with the proportion of water by as high as 25‐folds. Biofluorescence imaging experiments show that the probe TPE‐Cys has a good colocalization effect with the commercially available lysotracker red, with a Pearson correlation coefficient of 0.91. In addition, we also demonstrate that TPE‐Cys has good light stability. TPE‐Cys, as a neutral compound, is free of alkalinizing effect when applied in lysosome localization. Moreover, molecular dynamics simulations and density function theories are employed to explore the detailed aggregation process and the mechanism of TPE‐Cys aggregation in water solution. The mechanism of lysosome localization of probe TPE‐Cys was explained by cellular endocytosis process and the formation of larger particle in the more acidic environment of lysosomes. This work not only demonstrates an efficient strategy for the construction of fluorescent probes for lysosome localization, but also indicates that they are promising as live cell imaging tools. Abstract : Accurate localization of lysosomes is helpful to further study the pathological mechanism of related diseases. Zhang et al. designed and developed a novel neutral fluorescent probe with aggregation‐induced emission to enter cells through endocytosis for lysosome localization. An effective strategy of fluorescent probe for lysosome localization was constructed, which is expected to be used as a living cell imaging tool.